Flood Control On Secondary Sub Catchment Cerme Kidul In Drainage Systems Of Primary Canal Cerme Kidul kec. Cerme kab. Gresik - Muhammad Rangga Setya; Adi Prawito (Journal of World Conference (JWC), 2020)
Cerme District is located in South Gresik area which has an area of 71.73 km2. This area is located above the height of ± 4m sea level. While the slopes of the Cerme District are in the range 0-2% with a slope to the north. The land-use plan map of Cerme sub-district should be designated as an industrial area and residential area which is still inundated at several points. One of these puddles is in the left-hand cerme drainage system, especially in the secondary sub-catchment cerme kidul. The inundation height is between 20-30cm with inundation ± 2-4 hours. This final project can find out the results of the planned debit calculation using existing land use and land use plans, the difference in the calculation of the debit reaches 60%. While the calculation of canal capacity using planned land use can be known that 2 "safe" and 8 channel segments "need normalization".